ԿՈՄԻՏԱՍԻ. «Գարուն ա» երգի վերադրսևորումները Է. ՄԻՐԶՈՅԱՆԻ և Ա. ԲԱԲԱՋԱՆՅԱՆԻ ստեղծագործություններում - Պետրոսի Զուրաբյան, Ժաննա (Musical Armenia, 2011)
The analytical article of P.h.D candidate, Preofessor Yerevan Komitas named State Conservatory, Janna P. Zurabyna "The transformation of the song "Garun a" by Komitas in two compositions" is dedicated to the analysis of two classical works of Armenian music: string Quartet by Eduard Mirzoyan, written in 1947-48 and Piano Trio by Arno Babajanyan written 1952. In his conclusions the author gives a generalization temporary environment, analyzing the variation form of Mirzoyan's work and the traditional three-part form in Babajanyan's work. A thorough analysis in narrow and wide meaning of the word is presented. The article differs with deep penetration in the studied material.